Comparison of the horizontal positional accuracy of single base and network RTK within the mega-Manila sub-network - Reyes, Rosalie (Philippine Engineering Journal [eJournal])
Real Time Kinematic (RTK) Global Navigation Satellite System (GNSS) survey is a reliable and efficient survey method that has been used in applications that require centimeter level positioning in real time since the late 1900s. Two methods are commonly used for RTK positioning namely single-base RTK (SBRTK) and network RTK (NRTK). This research assessed the horizontal positional accuracy of SBRTK and NRTK with respect to derived positions using static positioning method. The Philippine Active Geodetic Network (PageNET) stations of the National Mapping and Resource Information Authority (NAMRIA), specifically the stations belonging in the Mega-Manila sub-network, were used as reference stations. Five (5) points with increasing distance from PTAG station were tested for this study in SBRTK method. Three techniques in NRTK were also experimented, namely : Virtual Reference System (VRS), Master Auxilliary Concept (MAC) and Flachen-Korrektur Parameter (FKP).